Promotion of the second National Report on Poverty and Social Exclusion in macedonia, 16th October 2012, Skopje - team, Editorial (Ревија за социјална политика/Journal of Social Policy, 2013)
With the goal of attaining continuity and developing further poverty and social exclusion analysis in Macedonia, the Macedonian Platform Against Poverty (MPAP) supported by the Ludwig Boltzmann Human Rights Institute - Research Association - Skopje (BIM-FV), promoted the Second National Report on Poverty and Social Exclusion in Macedonia, which analyzes policies, conditions and challenges in the field of poverty and social exclusion in Macedonia which were typical for year 2011. This, second Report, provides insight through regional analysis, of the situation with poverty and social exclusion in Macedonia.